Fiqh al-Bi’ah: Studi Historis Konsep Kebersihan dalam Literatur Fikih Klasik dan Kontemporer - Miftakhul Arif (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
The ecological crisis is a global problem caused by behavior that is not environmentally friendly. This is due, in part, to the perspective on the jurisprudence of cleanliness which tends to be theological-anthropocentric. This article attempts to examine the theoretical concept of the jurisprudence of cleanliness (t}aha>rah) in the works of fuqaha in the classical and contemporary eras. Data were collected from a number of works of classical and contemporary fuqaha and analyzed through content analysis techniques. The historical approach is used to find out the social background behind the fiqh theorization of cleanliness by classical and contemporary jurists. The results of the study concluded that there was a paradigm shift in understanding the concept of taharah. The classical era fuqaha approach in understanding the concept of taharah tends to be oriented towards ritual-theological meanings, only covering self-cleanliness from hadats and uncleanness. The theological orientation in understanding fiqh taharah has implications for the social attitudes of some Muslim communities who are ignorant of efforts to keep the environment clean. Contemporary jurists tend to use an ecological approach in understanding fiqh t}ah>rah in order to build theological awareness of the importance of protecting the environment. Differences in social and ecological backgrounds are the main factors behind the different interpretations of classical and contemporary jurists on the concept of taharah. At the end of the article, this article seeks to offer a synthesis in the form of a holistic concept of the jurisprudence of cleanliness with an anthropocosmic paradigm.